Lipid oxidation of fish meal stored under different storage conditions - Benjakul, S.; Laohabanjong, R.; Tantikitti, C. (Songklanakarin Journal of Science and Technology (SJST), 2007)
Changes of chemical quality and physical properties of fish meal due to lipid oxidation under different storage conditions were studied using a 3-factor factorial design (2x2x4). Premium grade fish meal (72%protein) was divided into two portions, with and without ethoxyquin, each portion was then stored at either ambient temperature or 4oC for 0, 1.5, 3 and 4.5 months. The results showed no interaction between 3factors (supplemented with or without ethoxyquin, at 27-32oC and 4o and storage time) on protein, lipid and ash of fish meal. Peroxide value (PV) and anisidine value (AnV) increased with storage time with the highestvalue in the non-ethoxyquin sample stored at ambient temperature for 4.5 months. An increase of TBARS was found in non-ethoxyquin fish meal stored at both ambient temperature and 4oC with the highest valuein the sample stored at 4oC for 4.5 months. Storage conditions without ventilation/air circulation caused an accumulation of malonaldehyde in the fish meal storage at 4oC for a long period. FFA content was highestin the ethoxyquin treated fish meal stored at ambient temperature for 3 months. At 4.5 months, the nonethoxyquin fish meal stored at ambient temperature showed higher FFA content than other samples. Levels of TVN of samples stored at ambient temperature decreased with time but those stored at 4oC changed inan opposite direction, which could be explained by the similar phenomenon as the changes of TBARS value. Parameters tested by feed microscopic and simple chemical techniques did not show any difference among fish meal under studied conditions.